Inovasi Kelembagaan Musyawarah Dusun sebagai Katalis Partisipasi Substantif: Pelajaran dari Desa Bulumeduro dan Desa Bulujowo, Kecamatan Bancar, Kabupaten Tuban - Sika Indriyawati; Eko Budi Santoso (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This study examines institutional innovation through the Hamlet Deliberation Forum (Musyawarah Dusun/Musdus) as a mechanism for improving the quality of community participation in village development planning meetings (Musrenbangdes). Using a qualitative comparative case study approach in Bulumeduro Village (implementing Musdus; ±1,164 inhabitants) and Bulujowo Village (without Musdus; ±5,253 inhabitants) in Bancar District, Tuban Regency, this study analyzes how institutional forum design influences inclusiveness, the quality of deliberation, and the influence of participation on policy. Data were collected through in-depth interviews with 20 key informants, observations of Musdes/Musrenbangdes forums, and document analysis of the Village Government Work Plan (RKPDes), meeting minutes, official records, and attendance lists. The findings show that Musdus in Bulumeduro simultaneously increased neighborhood-unit (RT) representation (from 13% to 50%), shifted communication patterns from one-way communication to two-way deliberation, and established a feedback mechanism that created a self-reinforcing cycle of trust. Comparison with Bulujowo, which applies a single-forum model, reveals a three-level difference in participation typology (Pretty: Consultative vs. Interactive Participation) and a two-rung difference on Arnstein's Ladder of Citizen Participation (Consultation vs. Partnership). This study contributes to the literature on participatory institutional design by demonstrating that improvements in participation quality can begin with local institutional innovation without waiting for changes in national regulations, and that differences in population size create the need for structurally different forum designs.